Beastly Possessions: Animals in Victorian Consumer Culture - Amato, Sarah (University of Toronto Press, Scholarly Publishing Division, 2015)
InBeastly Possessions, Sarah Amato chronicles the unusual ways in which Victorians of every social class brought animals into their daily lives. Captured, bred, exhibited, collected, and sold, ordinary pets and exotic creatures - as well as their representations - became commodities within Victorian Britain's flourishing consumer culture. As a pet, an animal could be a companion, a living parlour decoration, and proof of a household's social and moral status. In the zoo, it could become a public pet, an object of curiosity, a symbol of empire, or even a consumer mascot. Either kind of animal might be painted, photographed, or stuffed as a taxidermic specimen. Using evidence ranging from pet-keeping manuals and scientific treatises to novels, guidebooks, and ephemera, this fascinating, well-illustrated study opens a window into an underexplored aspect of life in Victorian Britain.